Identification of Bioactive Compounds in Various Vinegars and Determination of Their Antimicrobial Properties Against Foodborne Microorganisms - Karatepe, Pinar; Akgöl, Müzeyyen; İncili, Gökhan Kürşad (My University, 2024)
The aim of this study was to determine the bioactive compounds in a variety of vinegars (date, fig, mulberry, black mulberry, and pomegranate) and to test their in vitro antimicrobial activity against major foodborne pathogenic bacteria. Organic acids, volatiles, individual phenolic and flavonoid compounds, total phenolic content (TPC) and pH values were identified in vinegars. In addition, minimum inhibitory concentration (MIC), minimum bactericidal and fungicidal concentration (MBC and MFC) and diameter of inhibition zones of vinegars were determined against Escherichia coli O157:H7, Escherichia coli, Listeria monocytogenes, Salmonella Typhimurium, Salmonella Enteritidis, Staphylococcus aureus and Aspergillus parasiticus. A total of five different organic acids, 33 to 51 volatiles, and 13 to 21 polyphenols were identified in the vinegars. The pH of the vinegars were found to range between 3.27 and 3.74, and the TPC values were determined to be between 96.74 and 982.61 mg GAE/L. The MIC, MBC, and diameter of inhibiton zones against the tested strains were determined to be between 1.56% and 20.83%, 6.25% and 50%, and 8.22 and 19.81 mm, respectively. The results of this study indicate that the vinegars have a diverse array of bioactive compounds at varying concentrations, which consequently displayed a range of antimicrobial activity against the tested strains. The black mulberry vinegar exhibited the highest antimicrobial activity compared to the other vinegars. In conclusion, vinegar can be employed as a natural preservative to enhance the microbiological quality and safety of foods.
Keywords: Mikrobiyoloji; Gıda Bilimi ve Teknolojisi; Veterinerlik